2013
DOI: 10.1002/oby.20445
|View full text |Cite
|
Sign up to set email alerts
|

Modeling metabolic syndrome through structural equations of metabolic traits, comorbid diseases, and GWAS variants

Abstract: Objective: To provide a quantitative map of relationships between metabolic traits, genome-wide association studies (GWAS) variants, metabolic syndrome (MetS), and metabolic diseases through factor analysis and structural equation modeling (SEM). Design and Methods: Cross-sectional data were collected on 1,300 individuals from an eastern Adriatic Croatian island, including 14 anthropometric and biochemical traits, and diagnoses of type 2 diabetes, coronary heart disease, gout, kidney disease, and stroke. MetS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Both genetic and environmental factors play a role in the pathogenesis of MetS. Genetic studies of MetS have often shown that genetic predisposition is attributable to the individual traits rather than the syndrome as a whole and that MetS is a clinical rather than biological phenomenon [ 3 , 4 ]. However, genome-wide association studies (GWAS) for the individual components of MetS have reported the same loci as being associated with more than one MetS-related trait.…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic and environmental factors play a role in the pathogenesis of MetS. Genetic studies of MetS have often shown that genetic predisposition is attributable to the individual traits rather than the syndrome as a whole and that MetS is a clinical rather than biological phenomenon [ 3 , 4 ]. However, genome-wide association studies (GWAS) for the individual components of MetS have reported the same loci as being associated with more than one MetS-related trait.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al found 4 major factors of cardiovascular risk, including impaired glucose tolerance, dyslipidemia, hypertension and obesity, among non-diabetic elderly Korean individuals ( 22 ). In another study, through structural equation of metabolic traits, several indicators of abdominal obesity, body mass index, and also lipid and glucose observed variables were entered in the factor analysis; the 5-factor model was extracted and in fact, obesity and some measures of abdominal obesity were extracted as 2 separate factors ( 23 ). In contrast, Esteghamati et al found a single factor model in diabetic and non-diabetic population when TG and HDL were replaced by TG to HDL ratio, as an observed variable ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once predominantly used in genetics, econometric, and sociology, SEM applications have gradually shifted to the field of molecular biology [28]. For example, SEM has been used to explore alterations in gene networks in diseases [29,30], to provide a quantitative map of relationships between traits and disease [31], and to infer gene regulatory networks involving several hundred genes and eQTLs [32,33].…”
Section: Introductionmentioning
confidence: 99%